Manila 1870, seven years after the earth moved - Laya, Jaime C.
The scientific-minded Jesuits have long been keeping track of earthquakes. Number one on their record is the June 1, 1599 earthquake when the stone vault of the Jesuit church collapsed.
Keywords: Earthquakes; Earthquake chronology